The Effect Of Students’ Japanese Vocabulary On Their Comprehension Of Japanese Text - Soidy, O (Journal of Educational Method and Technology, 2019)
The aim of the study is to find out the impact of students’ mastery of Japanese vocabulary on their comprehension of Japanese text. The respondents were the students of Japanese Language Education Study Program at Manado State University. The study is an ex-post facto research. Data collection used vocabulary tests and reading comprehension tests. Data analysis was performed by correlation analysis with the coefficient of determination and simple regression analysis. The study results show that there is a positive and significant relationship between vocabulary mastery and reading comprehension skills of students of Japanese Language Education Study Program at Manado State University with a correlation coefficient of 0.613, R2 of 0.375, adjusted R of 0.373 with p <0.05, and correlation coefficient partially 0,151.